HUBUNGAN LITERASI KESEHATAN MENTAL DAN STIGMA DIRI DENGAN INTENSI MENCARI BANTUAN PADA REMAJA - Pakerti, Mar'ati Indah; Ariana , Atika Dian (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Adolescents are vulnerable to mental health problems, but this is not matched by the intention of reaching out to mental health professionals for help to their mental health problems. Low rates of help-seeking intentions are thought to be due to low levels of mental health literacy and high self-stigma related to help-seeking. This study aimed to examine the relationship between mental health literacy, self-stigma, and help-seeking intention in adolescents using a quantitative approach with survey methods. Involving 276 adolescent participants (aged 13–18), measurements were made using Mental Health Literacy (MHL), Self-Stigma of Seeking Help (SSOSH) and Mental Help Seeking Intention Scale (MHSIS). Results showed that there was evidence suggesting correlations between mental health literacy, self-stigma and help-seeking intention in adolescents.